Blizzards. - World Book, Inc. (Chicago : World Book, 2009)
"A discussion of a major type of natural disaster, including descriptions of some of the most destructive; explanations of these phenomena, what causes them, and where they occur; and information about how to prepare for and survive these forces of nature. Features include an activity, glossary, list of resources, and index"--Provided by publisher.
What is a blizzard? -- Blizards back in time -- Blizzard winds -- The school children's blizzard -- The Great White Hurricane of 1888 -- Blizzards and the human body -- Blizzards around the world -- Napoleon's grand retreat -- The White Hurricane of 1913 -- Storm damage -- After a blizzard -- Race to the South Pole -- Hard lessons of 1922 -- The Superstorm of 1993 -- Potomac aircrash -- The billion-dollar blizzard of 1996 -- Surviving a blizzard -- Chicago's?Big snow? of 1967 -- Blizzard rescue -- Forecasting blizzards.
Includes bibliographical references (p. 47) and index.
Keywords: Blizzards -- Juvenile literature